Optimasi Lahan Padi dan Jagung di Jawa Timur dengan Linear Programming - Pratama, Fatur Angga; Jumali, Muhamad Abdul (Metode : Jurnal Teknik Industri, 2026)
This study aims to determine the optimal allocation of planting areas for rice (X₁) and corn (X₂) in order to maximize agricultural profit in East Java Province. The agricultural sector in this region faces significant limitations in key resources, particularly land, fertilizer, and labor, which necessitate efficient and quantitatively grounded management strategies. This study employs a Linear Programming approach using the graphical method, based on a mathematical model developed from simulated data representing regional agricultural conditions. The results indicate that the optimal land allocation consists of 60 hectares for rice and 40 hectares for corn, generating a maximum profit of IDR 1,300,000,000. The constraint analysis reveals that land and fertilizer constraints act as binding constraints at the optimal solution, while the labor constraint is non-binding. This finding implies that further profit improvements cannot be achieved by increasing labor input, but rather by expanding or optimizing land use and fertilizer availability. Overall, this study provides a clear analytical framework to support decision-makers in formulating more efficient land allocation policies and improving agricultural productivity through optimal resource utilization